2004
DOI: 10.1001/archpedi.158.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Use of Safe Cribs and Bedroom Size Among African American Infants With a High Rate of Bed Sharing

Abstract: Crowding is not a strong explanation for bed sharing among impoverished African American infants in St Louis, Mo, who often bed share because there is not a safe crib available. Providing safe cribs may reduce the prevalence of bed sharing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Vemulapalli, Grady, and Kemp (2004) found that the lack of access to safe cribs, not cultural preference, was the primary reason for bed sharing among young African American mothers. Vemulapalli, Grady, and Kemp (2004) found that the lack of access to safe cribs, not cultural preference, was the primary reason for bed sharing among young African American mothers.…”
Section: Table 3 Establishing Healthy Sleep Hygiene Practicesmentioning
confidence: 95%
See 1 more Smart Citation
“…Vemulapalli, Grady, and Kemp (2004) found that the lack of access to safe cribs, not cultural preference, was the primary reason for bed sharing among young African American mothers. Vemulapalli, Grady, and Kemp (2004) found that the lack of access to safe cribs, not cultural preference, was the primary reason for bed sharing among young African American mothers.…”
Section: Table 3 Establishing Healthy Sleep Hygiene Practicesmentioning
confidence: 95%
“…Co-sleeping was associated with socioeconomics in African Americans in Missouri. Vemulapalli, Grady, and Kemp (2004) found that the lack of access to safe cribs, not cultural preference, was the primary reason for bed sharing among young African American mothers. In families of low socioeconomic status, sharing a sleeping space may be necessitated by a lack of available rooms in the house.…”
Section: Table 3 Establishing Healthy Sleep Hygiene Practicesmentioning
confidence: 95%
“…For instance, African American mothers from the District of Columbia area thought that infants would want bedding to be comfortable in the same way that adults would, and these mothers said that they used extra pillows and blankets to make the baby's sleep space cozy (Ajao, Oden, Joyner, & Moon, 2011). Another study of 100 African American mothers in St. Louis, Missouri, found a small number of parents using make-shift beds (e.g., laundry baskets, drawers, or woven bamboo baskets) that were lined with soft blankets for comfort (Vemulapalli, Grady, & Kemp, 2004). Interviews with 60 primarily African American mothers from Houston, Texas, also revealed that more than 80% knew that recommendations advised against soft bedding and stuffed animals in the baby's sleep space, but some propped up infants with pillows due to concerns about the baby rolling over or choking (Fowler, Evans, Etchegaray, Ottenbacher, & Arnold, 2013).…”
Section: Parental Management Of Perceived Riskmentioning
confidence: 99%
“…Research on breastfeeding mothers demonstrates that breastfeeding mothers sleep with their infants differently and more safely than bottle‐feeding mothers because a breastfeeding mother places baby under her arm and on baby’s back, and the mother tucks her knees to envelope the infant (Ball, 2003). On the other hand, bedsharing may not always be a personal choice but rather due to the fact that impoverished families may not have access to safe cribs (Vemalapulli et al, 2004).…”
Section: The Controversymentioning
confidence: 99%
“…Other groups advocate placing an infant alone in a crib where it cannot be smothered by adult blankets and pillows or the mother’s or father’s body. When bedsharing is practiced unsafely, crib sleeping offers a safer alternative (Vemulapalli, Grady, & Kemp, 2004). However, most infant mortalities during sleep occur when a parent leaves an infant to sleep alone, outside the sensory contact of a parent or responsible and committed adult (Drago & Dannenberg, 1999).…”
mentioning
confidence: 99%